ROLE OF GENITIC FACTORS IN PATHOGENESIS WITH COMPLICATED DUODENAL ULCER WITH BLEEDING - Oktyabr R. Teshaev; Olimboy M. Mavlonov; Sukhrob U. Alimov (Central Asian Journal of Medicine, 2022)
Aim: Study N-acetyltransferase activity and type of acetylation in patients with and without complication of ulcer disease. Methods: N-acetyltransferase activity and type of acetylation were studied in 163 patients; of these 63 had noncomplicated and 65 had complicated ulcer disease, while 35 were healthy (control group). Eighteen patients with complicated ulcer disease had perforation, 18 bleeding, and 29 stenosis. Results: In our studies, in the examination of patients with complicated course of peptic ulcer disease according to the most important clinical symptoms, a relationship was found between the activity of the acetylation process and clinical and laboratory indicators of peptic ulcer complicated by bleeding, perforation, and pyloroduodenal stenosis. Conclusion: Our results suggest that it would be useful to identify acetylation phenotype to aid prediction of the character and clinical course of gastric and duodenal ulcer disease. Peptic ulcer is a chronic recurring polyetiological disease that occurs as a result of the interaction of exogenous and endogenous factors: a hereditary predisposition from 5.5 to 50%, the type of nervous system, endocrine systems, psychoemotional features, metabolic characteristics, biochemical reactions, immune status, cytokine profile and environmental factors, resulting in a violation between the factors of “aggression” and “protection” of the mucous membrane of the gastroduodenal zone. In the etiology of peptic ulcer, a certain role is played by hereditary burden. Therefore, when studying the nature of the hereditary predisposition to peptic ulcer of the stomach and duodenum, an important area is the identification of genetic markers.